Embedding higher order thinking skills in Islamic history (Sirah) education in Malaysia - Muhammad Talhah Ajmain@Jima’ain; Ahmad Marzuki Mohamed; Aminudin Hehsan; Aminabibi Saidalvi; Badlihisham Mohd Nasir; Muhammad Sobri Faisal; Fareed Awae (Institute of Advanced Engineering and Science, 2024)
The promotion of integrating higher order thinking skills (HOTS) in the Malaysian education system is pivotal to producing analytical thinkers to keep up with the rapid globalization of this era. Thus, the implementation of HOTS in learning and facilitation (PdPc) has been emphasized. However, little is known about the integration of HOTS in Islamic history and civilization (Sirah) lessons. Furthermore, teachers continue to use traditional methods and disregard incorporating HOTS in PdPc. Therefore, the current study conducted an in-depth investigation into the components of Sirah lessons to support the implementation of the Malaysian education development plan (PPPM) 2013-2015 by strengthening teaching techniques through the use of HOTS for a better understanding of Sirah lessons. Using an explanatory sequential mixed method design, the findings reveal that the teaching components of Sirah lessons with the integration of HOTS are at a moderate level in the conclusion stage of a lesson. Therefore, the current study proposes a model that integrates HOTS, i.e., the element of attitude, preparation and planning, teaching aids with relevant aspects of PAK21, knowledge of HOTS, mastery of the subject content, teaching techniques and approach, assessment, and evaluation.